Characteristics of the Epididymal Luminal Environment Responsible for Sperm Maturation and Storage - Zhou, Wei; De Iuliis, Geoffry N.; Dun, Matthew D.; Nixon, Brett (Frontiers in Endocrinology, 2018)
The testicular spermatozoa of all mammalian species are considered functionally immature owing to their inability to swim in a progressive manner and engage in productive interactions with the cumulus oocyte complex. The ability to express these key functional attributes develops progressively during the cells’ descent through the epididymis, a highly specialized ductal system that forms an integral part of the male reproductive tract. The functional maturation of the spermatozoon is achieved via continuous interactions with the epididymal luminal microenvironment and remarkably, occurs in the complete absence of de novo gene transcription or protein translation. Compositional analysis of the luminal fluids collected from the epididymis of a variety of species has revealed the complexity of this milieu, with a diversity of inorganic ions, proteins, and small non-coding RNA transcripts having been identified to date. Notably, both the quantitative and qualitative profile each of these different luminal elements display substantial segment-to-segment variation which in turn contribute to the regionalized functionality of this long tubule. Thus, spermatozoa acquire functional maturity in the proximal segments before being stored in a quiescent state in the distal segment in preparation for ejaculation. Such marked division of labor is achieved via the combined secretory and absorptive activity of the epithelial cells lining each segment. Here, we review our current understanding of the molecular mechanisms that exert influence over the unique intraluminal environment of the epididymis, with a particular focus on vesicle-dependent mechanisms that facilitate intracellular communication between the epididymal soma and maturing sperm cell population.